2020
DOI: 10.1186/s41235-020-00214-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of geographic scale on spatial learning

Abstract: Background: Investigating the relationship between the human body and its spatial environment is a critical component in understanding the process of acquiring spatial knowledge. However, few empirical evaluations have looked at how the visual accessibility of an environment affects spatial learning. To address this gap, this paper focuses on geographic scale, defined as the spatial extent visually accessible from a single viewpoint. We present two experiments in which we manipulated geographic scale using two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Studies have demonstrated that human spatial abilities are not uniform across different scales (58); for example, being good at manipulating small objects does not necessarily make one good at navigating a campus (59). Zhao et al (60) investigated how spatial abilities interact with viewing perspectives in a large-scale environment. Participants navigated a virtual maze through 360 • images taken at normal eye level (ground perspective) or 360 • images taken at 5.3 metres above ground (elevated perspective).…”
Section: Individual Differences In Spa Al Learningmentioning
confidence: 99%
“…Studies have demonstrated that human spatial abilities are not uniform across different scales (58); for example, being good at manipulating small objects does not necessarily make one good at navigating a campus (59). Zhao et al (60) investigated how spatial abilities interact with viewing perspectives in a large-scale environment. Participants navigated a virtual maze through 360 • images taken at normal eye level (ground perspective) or 360 • images taken at 5.3 metres above ground (elevated perspective).…”
Section: Individual Differences In Spa Al Learningmentioning
confidence: 99%
“…Research on virtual learning environments has shown that the immersive, interactive, and 3D nature of iVR can potentially reduce the performance gap between students with high and low spatial abilities (Simpson et al, 2017;Lages and Bowman, 2018), which have been shown critical for STEM education (Newcombe, 2010). Immersive 3D visualizations can demonstrate the extent of landscapes and geological features in a form that is beneficial for students to develop spatial thinking, as they closely mirror everyday perceptual experience (Simpson, 2020). This mirroring capability is important in the context of the current study where students expressed preference for a more real-world experience.…”
Section: Outlook: Advancing Inclusivity Accessibility and Realismmentioning
confidence: 94%
“…In addition, current iVR technology allows for the integration of high-fidelity perceptual information (e.g., position, orientation, shape, size, or motion) and additional abstract information (e.g., video, graphs, and text) into a single virtual environment, which would enable the teaching of complex geological concepts through understandable visual demonstrations (Bowman et al, 2003). Such explicit graphical presentations might act as a "cognitive prosthetic" for students with lower spatial ability (Mayer and Sims, 1994;Höffler and Leutner, 2011;Jamieson et al, 2014;Zhao et al, 2020); that is, low-ability learners could gain a particular benefit from accessing an information-rich iVR environment, as they have difficulty mentally constructing their own representation when learning about geological features and processes from the textbook or a traditional field trip alone. This is also important for the present study, as it has been shown that lowspatial-ability learners can benefit more from a desktop VR application in comparison with high-spatial-ability learners (Lee et al, 2009).…”
Section: Outlook: Advancing Inclusivity Accessibility and Realismmentioning
confidence: 99%
“…Jin et al (2007) explained that 3-D visualization increases virtual imagery compared to traditional advertising. Similarly, AR interactivity helps customers understand the virtual environment in realtime (Zhao et al, 2020). Thus, interactive AR is emerging as an effective tool that enhances product experiences by educating the consumer and is effective in the shopping experience.…”
Section: Innovativenessmentioning
confidence: 99%